High performance ethanol sensor for control drunken driving based on flame-made ZnO nanoparticles - Liewhiran C. (2014)
ZnO nanoparticles were produced by FSP using zinc naphthenate as a precursor dissolved in toluene/acetonitrile (80/20 vol%). The phase and crystallite size were analyzed by Xray diffraction (XRD), and the specific surface area (SSA) of the nanoparticles was measured by nitrogen adsorption (BET analysis). The ZnO particle size and morphologies was further investigated by transmission electron microscopy (TEM) revealing spheroidal, hexagonal, and rod-like morphologies. The crystallite sizes of ZnO spheroidal and hexagonal particles were in the range of 10-20 nm. ZnO nanorods were found to be ranging from 10-20 nm in width and 20-50 nm in length. Sensing films were produced by mixing the particles into an organic paste composed of terpineol and ethyl cellulose as a vehicle binder. The paste was doctor-bladed onto A1 2O3 substrates interdigitated with Au electrodes. The morphology of the sensing films was analyzed by scanning electron microscopy (SEM). The gas sensing of ethanol (25-250 ppm) was studied at 400 °C in dry air. The oxidation of ethanol on the surface of the semiconductor was confirmed by mass spectroscopy (MS). Thick (5 μm) ZnO films showed high sensitivity and fast response times (within seconds). The sensitivity increased and the response time decreased with increasing ethanol concentration. These concentrations (25-250 ppm) were corresponded to be almost in the same range with detection limit of concentration for human breath analyzer. These sensor can be performed an ethanol sensing device that could be employed for control of drunken driving. © 2007 IEEE.